The Transformation of Women in Politics: From Symbolic Representation to Substantive Roles - Astuti, Widya; Afrilia, Merina; Amalia, Dea Rizky; Mulka, Sry Reski (Martabat: Jurnal Perempuan dan Anak, 2025)
This article examines the evolution of the political role of women in Indonesia, particularly in South Sulawesi, from symbolic representation to substantive political power. This transformation began with the 30% quota policy for women's representation, but more profound changes occurred when political parties started implementing selection mechanisms based on capacity and meritocracy. Using a qualitative-descriptive approach through literature analysis and case studies of female political figures in South Sulawesi, this study explores the internal dynamics of parties, social capital, and feminist leadership styles that influence women's substantive positions. The findings indicate that women can navigate patriarchal and patronage cultures through a combination of individual capacity, institutional support, and local legitimacy. Figures such as Husniah Talenrang, Andi Ina Kartika Sari, and Risfayanti Muin reflect a collaborative and empathetic leadership model that strengthens women's political influence. This study confirms the shift in women's politics from mere quantitative presence to strategic roles in decision-making. Nationally, this transformation is also reinforced by increased technocratic capacity, gender-inclusive cadre reforms, and cross-party solidarity networks that collectively promote women's politics as a transformative force for Indonesian democracy.